Attitudes toward Concealed Carry of Firearms on Campus: A Systematic Review of the Literature. (2nd January 2020) - Hassett, Matthew R.; Kim, Bitna; Seo, Chunghyeon
ABSTRACT: Gun control is a highly debated and divisive social issue. In recent years, this issue has been thrust into the academic arena with the advent of campus carry legislation and policies. Researchers have taken up the task of attempting to better understand the attitudes of those most affected by campus carry legislation – the campus community. The current project is a systematic review to synthesize 17 existing empirical studies regarding the attitudes of campus carry. Specifically, all published studies that examine the extent to which students and faculty/staff support or oppose campus carry and the factors underlying their attitudes were considered in the narrative review. Findings indicate that while a majority of individuals in the campus community are opposed to campus carry, the studies displayed a considerable degree of variation in campus carry attitudes based upon demographic variables, gun ownership, and fear of campus crime. With a thorough review of the literature and discussion of implications, a clear path for future inquiry and policymaking are presented.